2017
DOI: 10.1007/s11060-017-2459-z
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing-based genomic profiling of brain metastases of primary ovarian cancer identifies high number of BRCA-mutations

Abstract: Ovarian cancer represents the most common gynaecological malignancy and has the highest mortality of all female reproductive cancers. It has a rare predilection to develop brain metastases (BM). In this study, we evaluated the mutational profile of ovarian cancer metastases through Next-Generation Sequencing (NGS) with the aim of identifying potential clinically actionable genetic alterations with options for small molecule targeted therapy. Library preparation was conducted using Illumina TruSight Rapid Captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…25 Balendran et al reported a high rate of BRCA1 or BRCA2 mutations detected in the brain metastases of patients with ovarian cancer. 26 Of interest, platinum agents have demonstrated efficacy against brain metastases across many tumor types, including breast cancer, suggesting vulnerability of brain metastases to DNAdamaging agents. 27,28 Notably, our study included patients who received treatment before the regulatory approval of PARP inhibitors for the treatment of metastatic, BRCA1-associated or BRCA2-associated breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…25 Balendran et al reported a high rate of BRCA1 or BRCA2 mutations detected in the brain metastases of patients with ovarian cancer. 26 Of interest, platinum agents have demonstrated efficacy against brain metastases across many tumor types, including breast cancer, suggesting vulnerability of brain metastases to DNAdamaging agents. 27,28 Notably, our study included patients who received treatment before the regulatory approval of PARP inhibitors for the treatment of metastatic, BRCA1-associated or BRCA2-associated breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Higher proportion of BRCA1 (Sekine et al 27 4/7 patients) and BRCA1/2 (Balendran et al, 28 7/8 patients) mutation suggested potential role of BRCA mutation in ovarian cancer metastasizing to brain. …”
Section: Future Directionsmentioning
confidence: 98%
“…Few clinical and molecular factors have been studied, such as CD133 overexpression and platinum resistance (18), overexpression of MDR-1 (multi drug resistance 1) (19), having suffered from a previous breast cancer (20), loss of BRCA function (21) and, presence of mutations in BRCA1 and BRCA2 genes (22). In our work we explored the predictive and prognostic role of AR.…”
Section: Discussionmentioning
confidence: 99%